USE OF 1-ANILINO-8-NAPTHALENESULPHONATE AS AN ION PROBE FOR THE POTENTIOMETRIC STUDY OF THE BINDING OF SULFONAMIDES TO BOVINE SERUM-ALBUMIN AND PLASMA - Angelakou, A; Valsami, G.; Koupparis, M.; Macheras, P. (JOURNAL OF PHARMACY AND PHARMACOLOGY, 1993)
The binding of sulphafurazole, sulphamethizole and sulphamethoxazole to bovine serum albumin (BSA) and human plasma has been studied in-vitro by potentiometry using an electrode selective for the ion probe 1-anilino-8-napthalenesulphonate (ANS). The method requires two separate potentiometric titrations of the binder solution with ANS in the absence and in the presence of sulphonamides. ANS displaced sulphonamides from the first-class of binding sites of both binders. The binding constants for sulphonamide-BSA interactions were higher than those for sulphonamide-human plasma. The expansion of the least linear limit of the response curve of the electrode down to 10(-7) M in the presence of BSA was also demonstrated. The reverse reaction, i.e. the displacement of the probe from the binding sites induced by the sulphonamides, was also explored. The proposed method is suitable for studying competitive binding interactions in biological specimens.